Prevention of phencyclidine-induced depression of the segmental reflex by L-3,4-dihydroxyphenylalanine in the rat spinal cord in vitro. - Jonathan S. Carp; Ohno, Y.; Warnick, J. E. (The Journal of pharmacology and experimental therapeutics, 1989)
The interaction between phencyclidine (PCP) and the catecholamine precursor L-3,4-dihydroxyphenylalanine (DOPA) was studied in the isolated spinal cord from neonatal rats. PCP decreased the magnitude of the dorsal-ventral reflex and enhanced frequency-dependent depression of the reflex in a concentration-dependent manner. Although DOPA and DL-threo-3,4-dihydroxyphenylserine (a direct precursor for norepinephrine) had no effect on the reflex by themselves, DOPA, but not DL-threo-3,4-dihydroxyphenylserine prevented the depression of the reflex response by PCP in a concentration-dependent manner. Inhibition of aromatic-L-amino-acid decarboxylase (EC 4.1.1.2A) by m-hydroxybenzylhydrazine markedly attenuated the action of DOPA in preventing the depression caused by PCP. The dopamine receptor antagonists haloperidol and chlorpromazine blocked the action of DOPA, but the alpha and beta adrenergic receptor antagonists phentolamine and timolol, respectively, did not. In addition, prior treatment of neonatal rats with 6-hydroxydopamine diminished the ability of DOPA to prevent the depressant effect of PCP whereas partially attenuating the depressant effect of PCP alone. These results suggest that DOPA attenuated PCP-induced depression of spinal cord transmission through its conversion to dopamine rather than norepinephrine.
Keywords: Spinal Cord